Ab interno trabeculotomy with vs. without cataract surgery for POAG: a retrospective study - Lei Zhang; Junjie Bian (Frontiers in Medicine, 2026)
Purpose To compare the 12-month efficacy and safety of ab interno trabeculotomy combined with phacoemulsification vs. ab interno trabeculotomy alone in patients with primary open-angle glaucoma(POAG). Methods A retrospective analysis was performed on clinical data from patients diagnosed with POAG between January 2021 and January 2025 who underwent either combined surgery (combined group, 39 cases)or ab interno trabeculotomy alone (ab interno trabeculotomy-only group,44 cases). The primary outcome measures were postoperative intraocular pressure (IOP) and the change in IOP from baseline. Secondary outcomes included the number of antiglaucoma medications, surgical success rates (complete success and qualified success), and the incidence of complications (hyphema and IOP spike). Results Baseline characteristics were comparable between the two groups. At postoperative day 1, week 1, months 1, 3, and 6, IOP in the combined group was significantly lower than that in the ab interno trabeculotomy-only group (all P < 0.05). At 12 months postoperatively, no statistically significant difference in IOP was observed between the groups (15.94 ± 1.45 mmHg vs. 16.15 ± 1.36 mmHg, P = 0.266). The magnitude of IOP reduction was greater in the combined group than in the ab interno trabeculotomy-only group at all time points (all P < 0.05). No statistically significant differences were found between the two groups regarding the number of antiglaucoma medications or the reduction in medication use at any postoperative time point (all P > 0.05). At 12 months postoperatively, neither complete nor qualified success rates differed significantly between the groups. The incidence of hyphema was lower in the combined group than in the ab interno trabeculotomy-only group (23.08% vs. 43.18%, P = 0.053), and the incidence of IOP spike was significantly lower in the combined group (12.82% vs. 38.63%, P = 0.005). Conclusion In patients with POAG, combined ab interno trabeculotomy with phacoemulsification achieved superior IOP reduction and a significantly lower IOP spike rate compared with trabeculotomy alone. However, no statistically significant differences were observed at medication reduction, or surgical success rates. Given the retrospective, non-randomized design and baseline imbalances, the combined procedure cannot be definitively recommended as the preferred approach. These findings should be considered hypothesis-generating, and prospective randomized trials are warranted to validate them.